Arabidopsis FHY3 and FAR1 Regulate the Balance between Growth and Defense Responses under Shade Conditions. Issue 9 (16th July 2019) - Liu, Yang; Wei, Hongbin; Ma, Mengdi; Li, Quanquan; Kong, Dexin; Sun, Juan; Ma, Xiaojing; Wang, Baobao; Chen, Cuixia; Xie, Yurong; Wang, Haiyang
Abstract : The jasmonic acid signaling repressor proteins JAZs physically interact with FHY3 and FAR1 and repress their transcriptional activity, thereby prioritizing growth over defense under shade. Abstract: Increasing crop yield per unit of area can be achieved by increasing planting density. However, high-density planting could trigger shade avoidance responses, which cause exaggerated growth and increased susceptibility to various diseases. Previous studies have shown that the rapid elongation of plants under shade (i.e., reduced red to far-red ratios) is regulated by phytochromes and various phytohormones. However, the detailed molecular mechanisms governing the interaction among these signaling pathways are not well understood. Here, we report that loss-of-function mutants of FAR-RED ELONGATED HYPOCOTYL3 ( FHY3 ) and FAR-RED-IMPAIRED RESPONSE1 ( FAR1 ), which encode two homologous transcription factors essential for phytochrome signaling, exhibit an exaggerated shade avoidance phenotype. We show that FHY3 and FAR1 repress plant growth through directly activating the expression of two atypical basic helix-loop-helix transcriptional cofactors, PHYTOCHROME RAPIDLY REGULATED1 ( PAR1 ) and PAR2, and that this process is antagonized by a group of JASMONATE ZIM-DOMAIN proteins, key repressors of the jasmonic acid (JA) signaling pathway, through physical interactions. Furthermore, we show that FHY3 interacts with MYC2, a key transcriptional regulator of JA responses, coordinately regulating JA-responsive defense gene expression. Our results unveil a previously unrecognized mechanism whereby plants balance their growth and defense responses through convergence of the phytochrome signaling pathway and JA signaling pathway under shade conditions.